Analysis of CDR3 region diversity with different lengths in bovine immunoglobulin heavy chain genes - Zhao, Haidong; Tang, Xiaoqin; Zhang, Yuelang; Wu, Mingli (Frontiers in Immunology, 2025)
IntroductionCattle produce a unique antibody repertoire characterized by an exceptionally wide range of complementarity determining region 3 heavy chain (CDR3H) lengths, spanning from 1 bp to 204 bp—a feature that is extremely rare among mammals. The diversity characteristics of CDR3 segments of varying lengths and the underlying genetic and structural mechanisms remain an active area of research.MethodsWe constructed CDR3 expression libraries from splenic tissues of eight adult cattle using RACE-PCR, followed by high-throughput sequencing. CDR3 regions were analyzed statistically in accordance with IMGT standards and structural characteristics of immunoglobulins.ResultsHigh-throughput sequencing yielded a total of 473,067 high-quality reads. The CDR3 regions exhibited a broad length distribution, with the maximum reaching 234 bp. Based on density stacking analysis, CDR3 lengths were classified into four distinct groups: short (1~30 bp; 11.91%~16.93%), normal (31~100 bp; 81.51%~85.02%), long (101~150 bp; 0.12%~0.30%), and ultra-long (>150 bp; 0.16%~2.76%). Based on IMGT standards analysis, non-templated (N) nucleotides is the primary factor influencing CDR3 length. Each group displayed distinct preferences in V and D gene segment usage. The short CDR3 group was dominated by V1–14 and V1-39, the normal group was characterized predominantly by V1-39, while the long and ultra-long groups showed a strong preference for V1-7. Cattle possess two IgM subtypes, IgM1 and IgM2. The CDR3 length of the IgM1 subtype is primarily distributed in the short and normal groups. Within the normal CDR3 group, IgM1 exhibits a strong preference and exceptionally high utilization (70~80%) for the D4–1 gene segment. This stands in stark contrast to the usage of other D gene segments, particularly D8-2, which participates in CDR3 formation at a much lower frequency of merely 5~20%.DiscussionIn summary, our findings suggest that the diversification of bovine CDR3H length is a multifactorial process. It results not only from biased V(D)J recombination but is also influenced by the balance between exonuclease and TdT activities, specialized subregions within germline gene segments, N/P nucleotide insertions, stochastic trimming of gene ends, and the formation of unique structural motifs such as disulfide bonds. These findings provide a foundational model for understanding the architecture and generation of complex antibody repertoires.